Establishment constraints of an alien and a native conifer in different habitats - Carrillo-Gavilan, Amparo; MARÍA ESPELTA, JOSEP; Vila, Montserrat (BIOLOGICAL INVASIONS, 2012)
Alien plants are subjected to different biotic and environmental barriers that limit their establishment success in the introduced range. Pseudotsuga menziesii (Douglas fir), a native conifer from Northwest America, is considered one of the most invasive forestry conifers in Europe. However, little is known about the ecological filters that constrain plant establishment at early life-cycle stages and differences in habitat invasibility to this species. We conducted field experiments to compare the establishment potential (i.e. post-dispersal seed removal, seed germination, seedling survival and growth) of Douglas fir in beech forests, holm-oak forests and heathlands; and compared it with the taxonomically close native conifer Abies alba (Silver fir). Douglas fir seeds were more removed than Silver fir in holm-oak and in heathlands. In all habitats, seed germination was significantly higher for Douglas fir compared to that of Silver fir and, seedling mortality was extremely high in both species due to soil disturbance by wild boars and drought stress. Douglas fir mortality was only lower than Silver fir in beech forests. However, species did not differ in seedling growth. Overall, the probability of invasion success of Douglas fir decreased along the sequential stages of plant establishment in all habitats. Only high seed germination rates of Douglas fir would predict its high invasive capacity but these advantages are counterbalanced by high seedling mortality. Results showed a mismatch between invasibility and current pattern of Douglas fir invasion in the study area. Therefore, future research focused on seed production and on different components of biotic resistance is recommended to elucidate which processes are favoring its establishment success.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: Abies alba; germination; Invasibility; Pseudotsuga menziesii; Seed removal; seedling survival

Masting in oaks: Disentangling the effect of flowering phenology, airborne pollen load and drought - Fernández-Martínez, Marcos; Belmonte, Jordina; MARÍA ESPELTA, JOSEP (Acta Oecologica, 2012)
Quercus species exhibit an extreme inter-annual variability in seed production often synchronized over large geographical areas (masting). Since this reproductive behavior is mostly observed in anemophilous plants, pollination efﬁciency is suggested as one hypothesis to explain it, although resource-based hypotheses are also suggested as alternatives. We analyzed the effect of ﬂowering phenology, airborne pollen presence and meteorological conditions in the pattern of acorn production in mixed evergreendeciduous oak forests (Quercus ilex and Quercus pubescens) in NE Spain for twelve years (1998e2009). In both oaks, higher temperatures advanced the onset of ﬂowering and increased the amount of airborne pollen. Nevertheless, inter-annual differences in pollen production did not inﬂuence acorn crop size. Acorn production was enhanced by a delay in ﬂowering onset in Q. ilex but not in Q. pubescens. This suggests that in perennial oaks a larger number of photosynthates produced before ﬂowering could beneﬁt reproduction while the lack of effects on deciduous oaks could be because these species ﬂush new leaves and ﬂowers at the same time. Notwithstanding this effect, spring water deﬁcit was the most relevant factor in explaining inter-annual variability in acorn production in both species. Considering that future climate scenarios predict progressive warmer and dryer spring seasons in the Mediterranean Basin, this might result in earlier onsets of ﬂowering and higher water deﬁcits that would constrain acorn production.
Keywords: acorns; Drought; Mediterranean; Pollination efﬁciency hypothesis; Quercus spp.; Resource-based hypotheses

Mismatch between the timing of oviposition and the seasonal optimum. The stochastic phenology of Mediterranean acorn weevils - Bonal, Raul; Muñoz, Alberto; MARÍA ESPELTA, JOSEP (Ecological Entomology, 2010)
1. The timing of reproduction is predicted to match the period of maximum food availability. In this sense, the case of many phytophagous insects in temperate regions is very illustrative, as their larvae usually depend on a resource only available for a limited period of time each year. 2. For 3 years the interactions between the weevil Curculio elephas and the Mediterranean Holm oak Quercus ilex were studied. Weevil larvae grow within the acorns, feeding on the cotyledons. The timing of oviposition will determine food availability for the larvae, as acorns stop growing once they are attacked. 3. Acorn temporal growing patterns did not change between years and food availability for larvae was at its highest in October, when temperature was still suitable for larval development. However, oviposition phenology did change between years. In 2002 females oviposited later, larvae grew within larger acorns, and their body mass was significantly higher than in 2003 or 2004, when females oviposited into early acorns. 4. Thus, weevils do not always adjust oviposition to the best possible feeding conditions for their offspring. Rather, they seem to maximise their own lifetime fitness, ovipositing as soon as they emerge in late summer. Emergence, in turn, depends strongly on stochastic events such as summer storms in the Mediterranean region. 5. Under a climate change perspective, the trend towards higher August rainfall recorded in our study area may alter oviposition phenology, with the subsequent cascade effects on weevil body size and fitness
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn; adult emergence; Curculio; oviposition; Phenology; stochastic events; Temperature; timing of reproduction